Student Anxiety towards the Impact of Covid-19 Pandemic and its Implication in Counseling Guidance Services - Sulaiman Sulaiman; Ahmad Yanizon; Ramdani Ramdani; Tamama Rofiqah (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2022)
Anxiety can manifest as a physiological response to anticipate problems that may arise, or as a disorder if excessive, such as the Covid 19 pandemic which affects student anxiety. The research method used Quantitative with a research population of 67 Counseling Guidance Students, then a sample of 34 students was taken. Sampling technique with simple random sampling. Data analysis techniques using the Percentage Technique. Based on the results of the percentage analysis, 8 (23%) students are in the category of very high student anxiety, 15 (44%) are in the high category and 7 (20)% are in the medium category. 3 (9%) students have a student anxiety level in the low category and 1 (4%) student has a student anxiety level in the very low category.